Proximal humerus fractures in COVID-19 lockdown: the experience of three orthopedics and traumatology departments in the first ten weeks of the Italian epidemic - Maniscalco, Pietro; ciatti, corrado; gattoni, serena; quattrini, fabrizio; puma pagliarello, calogero; patane', angela caterina; capelli, patrizio; banchini, filippo; rivera, fabrizio; sanna, francesco; nonne, daniela; di maggio, bruno; et al. (Acta Biomedica Atenei Parmensis, 2021)
Introduction: Coronavirus disease (CoVID-19) is causing millions of deaths worldwide and the crisis of the global healthcare system. Aim Of The Study: evaluate the preliminary impact of CoVID-19 in three Italian Orthopedics and Traumatology Departments in the first 10 weeks of the national lockdown. We focused on proximal humerus fractures, analyzing data and results in comparison with the same period of 2019. Materials And Methods: From February 22nd to May 3rd 2020, 55 patients were admitted to our departments for promixal humerus fractures. Our cohort of patients is composed by 13 males (23.6%) and 42 females (76.4%), with an average age of 73.8 ± 11.7 years (range 44 - 94). Trauma occurred at home in 43 cases (78.2%), by the roadside in 10 cases (18.2%), in a retirement home in 1 case (1.8%), and at work in 1 case (1.8%). We proposed surgical treatment in 15/55 cases, but 4 patients refused hospitalization, mainly because of the risk of contracting n-CoV19 infection. Results: We noticed a decrease in proximal humerus fractures compared to 2019 (-37.5%). Particularly, we observed a significant drop in traumas occurred on the road and at work respectively 23.9% and 3.4%% in 2019, and 18.2% and 1.8% in 2020, probably due to the consequences of the national lockdown. Sports traumas had a reset during the pandemic (6 cases in 2019, 0 in 2020). As consequence, surgical treatment had a decrease due to the reduction in number of fractures, indications and patient’s consent. Conclusion: The incidence of proximal humerus fractures had a significant reduction during CoVID-19 spread. We assume that the reasons of this reduction are to be found in the national lockdown (since March 10th, 2020) and Ministerial Decrees that limited the access to the E.R. only in case of severe traumas in order to avoid CoVID-19 spread.